2015
DOI: 10.1016/j.trivac.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a tetravalent dengue vaccine during a five-year follow-up period

Abstract: a b s t r a c tThis study assessed the safety and persistence of dengue neutralising antibodies for five years after administration of a recombinant live, attenuated, tetravalent dengue vaccine (TDV). Participants aged 2-45 years (n = 126) were randomised at a single centre in the Philippines to receive TDV vaccinations at months 0, 3-4, and 12 (TDV-TDV-TDV group) or licensed typhoid vaccination (TyVi) at month 0 and TDV at months 3-4 and 12 (TyVi-TDV-TDV group). Dengue antibodies were measured annually (plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…6,7 This is in contrast with another four-year immunogenicity and safety follow-up of CYD-TDV in participants aged 2-45 years in the Philippines, a country considered highly endemic for dengue, where GMTs remained similar to those observed at one year post-vaccination. 11 It is possible that exposure to circulating wild-type dengue may have boosted antibody levels across all serotypes during longer-term follow-up in the later study. Our study demonstrated a decrease in neutralizing antibody at one year after third vaccine dose and through follow-up, but the antibody level persistence was sustained above baseline levels.…”
Section: Discussionmentioning
confidence: 95%
“…6,7 This is in contrast with another four-year immunogenicity and safety follow-up of CYD-TDV in participants aged 2-45 years in the Philippines, a country considered highly endemic for dengue, where GMTs remained similar to those observed at one year post-vaccination. 11 It is possible that exposure to circulating wild-type dengue may have boosted antibody levels across all serotypes during longer-term follow-up in the later study. Our study demonstrated a decrease in neutralizing antibody at one year after third vaccine dose and through follow-up, but the antibody level persistence was sustained above baseline levels.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, in dengue-endemic areas, GMTs tend to decline in the first year after the last injection, but thereafter remain relatively stable up to 5 years after the three-dose schedule with annual fluctuations due to natural exposure to wild-type dengue, or other flaviviruses, contributing to antibody persistence in this setting. 17 For children living in endemic countries, including participants from the CYD64 study, the annual incidence of asymptomatic dengue infection was shown to be over four-times higher than for symptomatic dengue, with the incidence 14.8% and 3.4% for asymptomatic and symptomatic infection, respectively. 18 The present study had some limitations.…”
Section: Discussionmentioning
confidence: 97%
“…[2][3][4][5] While the efficacy of the vaccine is now established, few data are available on the longterm immune memory generated by this vaccine. 6 Such data are essential to decide if and when re-vaccination might be required. Because the vaccine is more efficacious in individuals with preexisting DENV immunity (plaque reduction neutralizing titers (PRNT50) of > 10) from previous DENV or related flavivirus infections, it can be assumed that protection relies on the expansion of pre-existing cross-reactive immune memory.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this large observation-based follow-up study, a longitudinal study by Capeding et al monitored neutralizing titers in children and adults vaccinated with CYD-TDV over a 5-year period following the last immunization. 6 A marked decline in neutralizing titers was observed over time in vaccinees that did not experience a natural dengue or flavivirus infection within the followup period. While neutralizing titers measured in the blood are a useful readout of DENV immunity, the correlation between neutralizing titers and protection is still not clear.…”
Section: Introductionmentioning
confidence: 95%